Urdu: Evolution, Influence, and Resilience in Indian Linguistic Landscape: Bahasa Urdu Evolusi, Pengaruh, dan Ketahanan dalam Lanskap Linguistik India - Bhattacharya, Deepak (Universitas Muhammadiyah Sidoarjo, 2023)
This study delves into the rich linguistic tapestry of Urdu, tracing its origins in Sanskrit grammar, its versatile phonetics, and its enduring presence from love poetry to revolutionary discourse. Emerging in India, Urdu played a pivotal role as the lingua franca in the historical Awadh kingdom and served as a vital conduit during the 1857 revolt. Its roots as Proto Urdu, or Hindvi, can be traced to imperial Delhi, prior to Aurangazeb's reign. Following the Indo-Pak partition, Urdu was adopted as the National Language of Pakistan. While the percentage of Urdu speakers in India has remained stable since 1950, its cultural significance has continued to flourish, with substantial governmental support for its promotion. This article underscores the enduring influence of Urdu on Indian society, from Bollywood's pivotal role in sustaining its prominence to its integration with Hindi, exemplified by the commendable linguistic proficiency exhibited by the Indian armed forces. This linguistic legacy remains a cornerstone of Indian identity and a formidable force in the realm of Indian politics, firmly rooted and enduring in its significance. Highlight: Urdu's Diverse Roots: This study uncovers the linguistic evolution of Urdu, revealing its diverse origins in Sanskrit grammar and its ability to adapt to various phonetic styles, shaping its enduring presence in poetry and political discourse. Urdu as a Historical Nexus: Emerging in India, Urdu served as a critical lingua franca in the Awadh kingdom and played a pivotal role during the tumultuous events of the 1857 revolt, highlighting its historical and sociopolitical significance. Urdu's Contemporary Influence: Despite linguistic demographics remaining stable, Urdu's cultural importance has flourished, supported by substantial governmental backing. Its integration with Hindi and its commendable proficiency within the Indian armed forces illustrate its enduring impact on Indian society and politics. Keyword: Urdu, Linguistic Heritage, Cultural Significance, Language Evolution, Indian Identity